Navigating pregnancy and early motherhood in prison: a thematic analysis of mothers' experiences - Diksha Sapkota; Susan Dennison; Jyai Allen; Jenny Gamble; Corrie Williams; Nomxolisi Malope-Rwodzi; Laura Baar; Janet Ransley; Tara Renae McGee (BMC, 2022)
Abstract Background Maternal imprisonment negatively impacts mothers and their children and is likely to have lifelong and intergenerational sequelae. In many jurisdictions nationally and internationally, young children (usually those less than 5 years) can reside with their mothers in prison. However, there is considerable debate regarding the impact of prison environments on incarcerated mothers and their children who are born, and/or raised in prison. Research to date on the pregnancy and mothering experiences of imprisoned mothers and their preferences for care arrangements for their babies and young children is limited. Methods This study was part of the Transforming Corrections to Transform Lives project, in which workshops were conducted with imprisoned mothers to understand their needs while in custody and post-release, and the kind of supports and system changes that are required to meet those needs. Incarcerated mothers (n = 75) participated in seven workshops conducted across four Queensland prisons. Themes were generated through reflexive thematic analysis. Results Three themes characterised mothers' experiences of being pregnant and undertaking a mothering role of a young child while in prison. First, for most mothers, imprisonment adds vulnerability and isolation during pregnancy and childbirth. Second, although mothers felt that residing together with their children in prison motivated them to change for a better future, they were concerned about the potential negative impact of the prison environment on the child's development. Lastly, most mothers voiced losing autonomy and agency to practice motherhood independently within custodial settings. Mothers expressed a need for the correctional system to be adapted, so it is better equipped to address the unique and additional needs of mothers with young children. Conclusion Mothers' experiences indicated that the correctional system and policies, which were predominantly designed for men, do not adequately address the varied and complex needs of pregnant women, mothers, and their young children. Imprisonment of pregnant women and mothers with young children should be the last resort, and they should be provided with holistic, individually tailored support, most preferably in community settings, to address their multiple intersecting needs.